Basking in detected vice: Outgroup immorality enhances self-view. (April 2021) - Sacchi, Simona; Brambilla, Marco; Graupmann, Verena
In the last decade, a growing body of research has revealed that morality is the most important driver of impression formation. As such, social targets lacking morality are disliked and kept at distance, while moral targets are liked and respected. Here, we investigated whether social targets lacking morality elicit positive reactions in the observer. Study 1 revealed that participants reported an enhanced self-view when confronted with an immoral (vs. moral) behavior performed by a political opponent. Study 2 revealed the key role of morality in this process, as differential perceptions of the target's incompetence had no comparable effect on the observer self-view. Importantly, such results emerged when participants were highly identified with their ingroup. Taken together, these findings suggest that outgroup immorality can elicit positive self-related responses in the observer. Results are discussed in terms of their theoretical and practical implications for social judgment and intergroup relations.